Direct Observation of Time-Dependent Coherent Chiral Tunneling Dynamics - Sun, Wenhao; Tikhonov, Denis S; Schnell, Melanie (Physical review letters, 2025)
Superpositions of handed molecular states give rise to achiral eigenstates, delocalized across a double-well potential via tunneling. A coherent superposition of these energy eigenstates could dynamically relocalize the molecules into chiral states, which has only been addressed theoretically. Here, we present a microwave pump-probe study to create and probe coherent chiral tunneling dynamics in a given rotational state. Through a time-resolved scheme, we uncover the periodic time evolution of the induced chiral wave packet under field-free conditions. Moreover, we demonstrate precise phase control of this coherence via phase modulation during pump excitation.